Incorporating Quality of Life Metrics in Interventional Oncology Practice - Li, David; Madoff, David C. (Seminars in Interventional Radiology, 2017)
Interventional radiologists care for a large number of cancer patients with the breadth of palliative intent minimally invasive procedures that we provide. Understanding our meaningful impact on patients' quality of life is essential toward validating our role in the palliation of cancer patients. As such, it is critically important for interventional radiologists to understand common instruments used for the reporting of patient's quality of life measures. Common instruments used to measure pain and quality of life for cancer patients include the numerical rating scale, visual analog scale, brief pain inventory, the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire, and the Functional Assessment of Cancer Therapy. An ideal quality of life instrument should be a patient reported outcome measure across multiple domains (e.g., physical health, psychological, social), and be both validated and reliable.
Keywords: palliative care; interventional radiology; quality of life; visual analog scale; numeric rating scale; brief pain inventory; EORTC-30; FACT-G